ANALYSIS ELEMENT OF ORGANIZATION CAPABILITY THAT EFFECT ON ORGANIZATION PERFORMANCE IN PT. KERETA API INDONESIA (PERSERO) (The Indonesian Journal of Business Administration, 2019)
PT. Kereta Api Indonesia (persero) is one of the state's own companies based on the transportation business. In 2017 the ministry of transportation (Menhub) with Kalimantan and Sulawesi Government build train transportation to meet the need for transportation. Train transportation will manage by PT. Kereta Api Indonesia at the end of 2019, so the company needs more employees to manage their new area. Analysis Capability of organizations needed to maintain their performance still good, so the company knows what element of capability that must be developed on their new employee and has a big impact on company performance. Methodology analysis using multiple regression analysis to know the relationship of organization capability to organization performance. 100 respondent was taken in this analysis is an employee of headquarter of PT. Kereta Api Indonesia (persero), This research use nine element (Speed, Innovation, Relationship with Customer, Seeks with related change, Strategic responsiveness, Talent, Efficient, Ready for strategic alliance, and international working environment) of organization capability that have impact to organization performance, from nine element which was analyzed with multiple regression analysis, there are 2 elements that has a big impact on organization performance this is working speed and international working environment. Speed has a significant level of 0,011 and a T value of 2,601, which means if the speed of an employee increase in one unit there is an increasing organization performance of 2,601. The international working environment has a significant level of 0,001 and a T value of 3,479, which means if the international working environment of PT. Kereta Api Indonesia (persero) increase in one unit so the organization's performance increases 3,479. Based on the interview and SWOT analysis of PT. Kereta Api Indonesia it can be concluded that changes must exist to maintain the existence of the company, but PT. Kereta Api Indonesia has a big challenge to prepare their human resource to be ready. PT. Kincreasesereta Api Indonesia has power as a stated own company, but if their employee is to relaxed and comfortable in their zone without any desire to change, their existence will falling down. Some implementations plan recommend PT. Kereta Api Indonesia to increase their readiness is Give training about creative and integrative thinkin, Make  list of common obstacle and how to solve, Make innovation that support the main product, Give employee english training and make ability to use english in office, Update information and issue in the internationl steel market and share by HRIS.Keywords : PT. Kereta Api Indonesia, Organization, Capability, Performance